Law and the Poor: Some Recent Developments in India - Jain, M.P. (Journal of Malaysian and Comparative Law, 2019)
The problem of poverty in India is pervasive and endemic. Leaders of the society have always been conscious of his problem and of the need to eradicate poverty. In the colonial days, this was one of the chief reasons for demanding the end of colonialism in India.